Mesenchymal Stem Cells Migration Homing and Tracking - Abhishek Sohni; Catherine M. Verfaillie (Stem Cells International)
In this review, we discuss the migration and homing ability of mesenchymal stem cells (MSCs) and MSC-like cells and factors influencing this. We also discuss studies related to the mechanism of migration and homing and the approaches undertaken to enhance it. Finally, we describe the different methods available and frequently used to track and identify the injected cells in vivo.